Analysis of factors influencing the effectiveness of contractor safety management system implementation on contractor’s OHS performance in oil and gas platform and jacket construction project PT. X Bintan - Waluyo, Edy; Wahyu, Atjo; Saleh, Lalu Muhammad; Naiem, M. Furqaan; Amqam, Hasnawati (Edelweiss Applied Science and Technology, 2026)
This study aims to examine the factors influencing the effectiveness of Contractor Safety Management System (CSMS) implementation and its direct and indirect effects on contractors’ occupational health and safety (OHS) performance in the PT X Oil and Gas Platform and Jacket Construction Project in Bintan Regency. A quantitative cross-sectional design was employed, involving 185 workers selected through proportionate stratified random sampling and analyzed using path analysis with AMOS. The findings show that safety culture (p=0.022), safety behavior (p<0.001), working conditions (p=0.007), and safety communication (p<0.001) significantly influence CSMS effectiveness, while resources and safety training do not show significant effects. In terms of OHS performance, safety culture (p=0.050), resources (p<0.001), safety communication (p=0.003), safety training (p=0.003), and CSMS effectiveness (estimate=0.559; p<0.001) demonstrate significant direct effects. CSMS effectiveness also mediates the relationship between several safety factors and OHS performance. The study concludes that effective CSMS implementation is the most influential factor in improving contractor OHS performance. Practically, strengthening safety culture, improving communication, promoting safe behavior, and ensuring adequate resources and training are essential to enhance safety performance in high-risk oil and gas construction projects.